XXIV ALLRUSSIA YOUTH CONFERENCE ON STRUCTURE OF LITHOSPHERE AND GEODYNAMICS, IRKUTSK, RUSSIA, APRIL 19–24, 2011 - Victoria A. Khak (Геодинамика и тектонофизика, 2015)
The information on the XXIV AllRussia youth conference on structure of lithosphere and geodynamics is presented. It was held on April 19–24, 2011 at the Institute of the Earth’s Crust, Irkutsk. The scope of conference is presented.